2015
DOI: 10.1016/j.joa.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of non‐vitamin K antagonist oral anticoagulant use in Japanese patients with atrial fibrillation: A single‐center observational study

Abstract: BackgroundNon-vitamin K antagonist oral anticoagulants (NOACs) show a favorable balance between efficacy and safety compared with warfarin for patients with non-valvular atrial fibrillation (NVAF). In “real-world” practice, however, NOAC adherence and persistence among patients are not clear. The aim of this study is to evaluate NOAC and warfarin persistence in Japanese patients with NVAF who newly started these drugs.MethodsWe retrospectively studied 401 patients with NVAF who had newly started NOACs during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
49
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 37 publications
(36 reference statements)
14
49
2
Order By: Relevance
“…Patients receiving NOACs had worse persistence than those prescribed warfarin in our study, which was consistent with Shiga's study in Japan (Shiga et al, ). In the RE‐LY trial, the rates of dabigatran discontinuation at 1 and 2 year were also reported to be higher than warfarin (Connolly et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Patients receiving NOACs had worse persistence than those prescribed warfarin in our study, which was consistent with Shiga's study in Japan (Shiga et al, ). In the RE‐LY trial, the rates of dabigatran discontinuation at 1 and 2 year were also reported to be higher than warfarin (Connolly et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…However, VKA adherence could not be reliably assessed due to dynamic dosing on claims data. While the literature reports mixed results on the comparative persistence of DOAC versus VKA, whether or not DOAC patients have better persistence rates than VKA patients in no way lessens the issue of poor adherence with DOACs, now recommended as first‐line treatment over VKA for stroke prevention . In contrast, for clinical practice, our results suggest that initiating DOAC as first‐line treatment might not necessarily result in good adherence in nv‐AF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, concerns have been raised about the potential impact of no monitoring and the presence of multimorbidity and polypharmacy on DOAC adherence . Knowledge about patients' adherence to DOACs in real life is however still limited, and studies conducted thus far differ in scale, methodology, and focus …”
Section: Introductionmentioning
confidence: 99%